The benefits of common inclusive identities for adolescent bystanders’ intentions to help homophobic bullying victims - António, R.; Guerra, R.; Moleiro, C. (Social Psychology of Education, 2024)
Bystanders’ helping behaviors are essential to mitigate bullying and its consequences, although bystanders do not always intervene on behalf of those who are victimized. One study (N = 170) tested, experimentally, the impact of different forms of common identities (one-group and dual-identity vs. control) on youth (aged between 12 and 19 years) bystanders’ helping behavioral intentions in the context of a common form of bias-based bullying (i.e., homophobic bullying). Results showed that dual-identity triggered more behavioral intentions to help victims of homophobic bullying. Overall, these findings extended previous studies illustrating the potential of common identities to foster bystanders’ helping responses to homophobic bullying episodes in the school context.